2016
DOI: 10.1051/limn/2016003
|View full text |Cite
|
Sign up to set email alerts
|

A multiple process univariate model for the prediction of chlorophyll-a concentration in river systems

Abstract: The concentration of chlorophyll-a (Chl-a) in river systems is dependent on various hydrometric and biochemical factors, including an intricate array of corresponding growth and extinction mechanisms. This complex and interactive assortment of factors makes prediction of algal blooms difficult. This paper introduces an innovative time-series model structure that predicts Chl-a concentration in inland waters. To improve the prediction accuracy of existing models, we assume that the predicting variable is determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Their results showed that rainfall, river flow, water temperature and nutrient concentration were the primary factors affecting cyanobacterial blooms in the study river system, suggesting that the successful control of cyanobacterial blooms requires integrated watershed management, accommodating the control and management of meteo-hydrological-physicochemical factors. Kim (2016) introduced an innovative time-series model to predict the chlorophyll-a concentration in Korean rivers. A multiple process univariate model, which is an enhanced stochastic model, was developed to address the effects of distinct mechanisms associated with hydrometeorological factors and anthropogenic activities.…”
Section: Water Quality and Algal Bloommentioning
confidence: 99%
“…Their results showed that rainfall, river flow, water temperature and nutrient concentration were the primary factors affecting cyanobacterial blooms in the study river system, suggesting that the successful control of cyanobacterial blooms requires integrated watershed management, accommodating the control and management of meteo-hydrological-physicochemical factors. Kim (2016) introduced an innovative time-series model to predict the chlorophyll-a concentration in Korean rivers. A multiple process univariate model, which is an enhanced stochastic model, was developed to address the effects of distinct mechanisms associated with hydrometeorological factors and anthropogenic activities.…”
Section: Water Quality and Algal Bloommentioning
confidence: 99%
“…Modeling chlorophyll dynamics in rivers can be challenging due to non‐linear relationships between chlorophyll and its drivers, as well as covariation or interaction among drivers. Multiple approaches have been used to model chlorophyll in rivers including process‐based (Billen et al., 1994; Everbecq, 2001; Pathak et al., 2021), traditional statistical (S. Kim, 2016; K. B. Kim et al., 2020), and machine learning (Cho et al., 2018; Jeong et al., 2001; Park et al., 2022). Although model objectives of predictive accuracy and process understanding are not mutually exclusive (Duarte et al., 2003), each modeling approach varies in its emphasis on these two components and has strengths and weaknesses for broad‐scale use.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling chlorophyll dynamics in rivers can be challenging due to non-linear relationships between chlorophyll and its drivers, as well as covariation or interaction among drivers. Multiple approaches have been used to model chlorophyll in rivers including process-based (Billen et al, 1994;Everbecq, 2001;Pathak et al, 2021), traditional statistical (S. Kim, 2016;K. B. Kim et al, 2020), and machine learning (Cho et al, 2018;Jeong et al, 2001;Park et al, 2022).…”
mentioning
confidence: 99%
“…The growth of HABs was successfully predicted using historical data and ecological informatics and applying DL methods [62]. The DL methods were also used to predict algal growth in rivers [63][64][65][66], lakes [67,68], and coastal areas [69,70]. However, these methods function as black boxes, and the neuron connections, their weights, and different layers cannot be associated much with the concept of the physical problem at hand [71].…”
Section: Introductionmentioning
confidence: 99%